Thermoelectrics of type-I and type-II nodal line semimetals within the two-band model - Jyesta Mahayu Adhidewata; Ahmad R. T. Nugraha; Eddwi Hesky Hasdeo; Bobby Eka Gunara (Indonesian Journal of Physics, 2022)
Metals and semimetals are often considered poor thermoelectric (TE) materials due to their lowSeebeck coefficients. However, we will show that topological semimetals in the class of nodal-linesemimetals (NLSs) may potentially exhibit better performance as TE materials. The NLSs are semimetalswith an intersection between the conduction band and valence band in the forms of a line (thus called thenodal line). We construct a two-band model using an almost-linear conduction and parabolic (or Mexicanhat) valence bands that overlap each other near the band edge to represent a type-I (or type-II) NLS. Wecalculate TE properties of the NLSs using the semiclassical Boltzmann transport theory and the relaxationtime approximation. By varying the band parameters in our model, we find that the type-II NLS generallyhas better TE performance than the type-I NLS. The type-II NLS, in particular, possesses a Seebeckcoefficient with a value possibly larger than twice that of normal metals. The origin of this feature mightbe the presence of a discontinuity in the density of states due to the intersection of the valence andconduction bands.